Evaluación de Propiedades Físicas y Mecánicas de una Matriz de Policaprolactona/Hidroxiapatita Obtenida por Impresión 3D - Fontalvo Suarez, Melvin Rafael; Cardona Muñoz, Juan David (Universidad Antonio Nariño, 2022)
The need to restore bone defects caused by periodontal disease or different traumas for the rehabilitation of edentulous areas with dental implants has led to the search for different techniques and a wide range of biomaterials. In order to enhance the physical, mechanical, and biological properties of biomaterials, the mix between natural and synthetic has meant that the benefits of each one are used for particular purposes. The use of polycaprolactone (PCL) and hydroxyapatite (Hap) has been defined as a biomaterial with a promising future associated with previous biological results reported. These materials have been used in elaborating membranes that serve as scaffolds to achieve said regeneration of bone tissues.